2000
DOI: 10.1002/1096-9071(200008)61:4<443::aid-jmv6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hepatitis C after liver transplantation

Abstract: Cirrhosis due to hepatitis C is now the commonest indication for liver transplantation in Western Europe and in the United States. Graft reinfection is almost universal. The natural history of recurrent hepatitis C ranges from minimal damage to cirrhosis in a few months or years. Different virus and host immune factors are involved in the pathogenesis of hepatitis and are determinants of the outcome. The association between immunosuppression and severity of HCV recurrence is conflicting and remains to be evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 107 publications
(164 reference statements)
0
18
0
Order By: Relevance
“…A tendency toward increase in serum HCV RNA levels seems to be associated with the early phase after transplantation when the use of immunosuppression is greatest and the use of a steroid bolus more frequent. In fact, Berenguer et al showed in an analysis based on the historic timing of transplantation more aggressive HCV recurrence in those patients who were given a shorter course of steroids [18][19][20]. Several factors within this analysis, including treatment variations among transplant teams and the increased use of marginal donors, may have affected their outcomes.…”
Section: The Effects Of Non-antiviral-related Strategies (Immunosupprmentioning
confidence: 98%
“…A tendency toward increase in serum HCV RNA levels seems to be associated with the early phase after transplantation when the use of immunosuppression is greatest and the use of a steroid bolus more frequent. In fact, Berenguer et al showed in an analysis based on the historic timing of transplantation more aggressive HCV recurrence in those patients who were given a shorter course of steroids [18][19][20]. Several factors within this analysis, including treatment variations among transplant teams and the increased use of marginal donors, may have affected their outcomes.…”
Section: The Effects Of Non-antiviral-related Strategies (Immunosupprmentioning
confidence: 98%
“…Approximately 20% of the patients develop cirrhosis at 5 years post-OLT 2,3 compared with a similar percentage or less who develop cirrhosis at 20 years in the pre-OLT setting. 4 Because not all patients post-OLT progress to fibrotic liver disease, at least in the medium term, many studies have evaluated such viral and host factors as donor and recipient age and sex, pre-OLT HCV concentration, HCV genotype, HCV quasispecies, donor and recipient histocompatibility, presence of coexisting liver disease (hepatitis B virus and hepatocellular carcinoma), type and dose of maintenance immunosuppression, and number of pulses of high-dose steroid therapy for treating rejection 5 that might predict progressive liver disease. A small group of patients develop a severe form of cholestatic hepatitis associated with a very high intracellular load and perhaps more quasispecies homogeneity.…”
Section: Irrhosis Caused By Hepatitis C Virus (Hcv) Infection Is Cumentioning
confidence: 99%
“…5 Once cirrhosis occurs, decompensation is rapid. 6 Graft reinfection is manifested by acute lobular hepatitis, usually asymptomatic 7 and diagnosed in more than 50% of patients between 2 and 6 months.…”
mentioning
confidence: 99%
“…Many studies have examined viral factors that might predict the course and outcome of recurrent HCV, 5 but apart from an association with viral load, 14 it is difficult to be sure whether the development of fibrosis, the key factor in recurrence, is related to viral factors. 5 Coinfection with cytomegalovirus (CMV) is disputed as a cofactor, [15][16][17] but obviously even despite prophylaxis, CMV infection would be more likely with a more powerful induction immunosuppression.…”
mentioning
confidence: 99%
See 1 more Smart Citation